Belief Change of Indonesian EFL Pre-Service Teachers during Teaching Practicum - Johanes, Sarah; Agustina, Noni (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2026)
This study explores belief change among five Indonesian EFL pre-service teachers during a teaching practicum, with particular attention to sociocultural influences (e.g., interactions with mentors, students, and the school environment). Using a qualitative design, the study collected data through semi-structured interviews conducted before and after a 40-day practicum and through classroom observations. The participants were seventh-semester students (aged 21–22) from the English Language Education Department of private university in West Jakarta, Indonesia who completed their practicum at public junior high school in West Jakarta. Data were transcribed, translated where necessary, and coded using Cabaroglu and Roberts’ (2000) belief-change categories. Findings indicate that all participants displayed patterns of belief change across the practicum. The most frequent coding outcome was no change (34%), followed by consolidation/confirmation (32.7%) and pseudo change (20.3%). No instances of re-labeling were identified across participants. These results suggest that while practicum experiences can reinforce and reshape certain beliefs, a substantial proportion of pre-service teachers’ beliefs remain stable, highlighting the need for structured mentoring and reflective opportunities during practicum